PUSAT PELATIHAN DAN PENGEMBANGAN ATLIT BULUTANGKIS DI KOTA PELAIHARI - Normariah, Normariah; Huzairin, Muhammad Deddy (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2023)
The Badminton Athlete Training and Development Center in Pelaihari City is a facility that accommodates training and development of athletes in badminton sports in Pelaihari city with national standards so that users can get adequate facilities in training to the fullest. Pelaihari City is the capital of Tanah Laut district in South Kalimantan, but there are still no adequate training building facilities so that badminton practice is often held in inadequate buildings with a poor system of facilities and infrastructure. This badminton training and development center is also equipped with library facilities as an athlete reading room, management room, cafe, and retail equipment for badminton equipment so that it can accommodate athletes or the surrounding community who want to learn badminton in the city of Pelaihari. With a building standard approach that is used to fulfill functions according to space standards.